Development of Interactive Learning Multimedia on Atomic Model Topic to Minimize Students Misconceptions at SMAN 1 Driyorejo - Rani Ratna Kusuma; Sukarmin Sukarmin (Universitas Pendidikan Mandalika, 2023)
This research aims to develop interactive multimedia that can minimize students' misunderstanding of atomic model materials. Media developed using Macromedia Flash which contains animations about atomic models. Feasibility is reviewed from three aspects, namely (1) validity which contains the validity of content and construct, (2) practicality which is reviewed based on the results of student observations and response questionnaires, (3) effectiveness reviewed based on pretest – posttest results which will later show a shift in student conception from initially not understanding the concept (TPK) to understanding the concept (PK). This research uses the 4D Research and Development (R&D) method with 15 research subjects in class XI Science at SMA Negeri 1 Driyorejo. The results of the research obtained show that interactive multimedia is suitable to be used as a medium in learning and minimizes the occurrence of misconceptions in atomic model material. This is evidenced based on the results obtained during the study, namely (1) the average validation obtained mode 5 so that it was categorized as very good / valid, (2) the average percentage of student response questionnaires obtained a score of 94% so that it was categorized as very practical, in observation a score of 98% was obtained so that it was categorized as very practical, (3) and the average percentage of student conception shift from not understanding the concept (TPK) to understanding the concept (PK) obtained a score of 87.23% so that it was included in the category is very effective.